APPLICATION OF TRAINING AND PRACTICE METHODS IN CALLIGRAPHY LEARNING TO IMPROVE ARABIC WRITING IN GRADE TEN AT AL-FAIZ ISLAMIC BOARDING SCHOOL IN MEDAN - Mellani, Mellani; Kamalia, Kamalia (Ihya al-Arabiyah: Jurnal Pendidikan Bahasa dan Sastra Arab, 2025)
In education, teachers play a very important role in designing learning activities to engage students and ensure that learning objectives are conveyed effectively. The purpose of this study was to determine the development of Arabic writing in students studying calligraphy. This study was conducted at the Al-Faiz Islamic boarding school in Medan. In this study, the researcher used a qualitative research method with a descriptive approach and data collection techniques in the form of observation and interviews. Observations were conducted on twenty female students in grade X at the Al-Faiz Islamic Boarding School in Medan. Based on an interview with calligraphy teacher Ustadz Abimanyu, "In calligraphy learning, there are many types and styles of calligraphy that need to be learned, not to mention the differences in letter shapes, curves, and angles when writing. In addition, the students come from various school backgrounds, which makes the main focus how to increase students' interest in learning calligraphy, so that interesting and non-monotonous methods are needed so that students do not get bored easily." The impact on education is that it can train writing skills (maharah kitabah). The results of the study indicate that calligraphy instruction at this school can be considered quite effective, as evidenced by the improvement in the quality of students' Arabic writing.